2017
DOI: 10.7759/cureus.1438
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Antioxidant Effects of Sesame Oil on Atherosclerosis: A Descriptive Literature Review

Abstract: Sesame oil (SO) is a supplement that has been known to have anti-inflammatory and antioxidant properties, which makes it effective for reducing atherosclerosis and the risk of cardiovascular disease. Due to the side effects of statins, the current recommended treatment for atherosclerosis and cardiovascular diseases, the idea of using dietary and nutritional supplementation has been explored. The benefits of a dietary health regime have piqued curiosity because many different cultures have reaped health benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…There were no significant changes in TBARS concentration within the groups; however, decreasing trend in TBARS concentration after SO treatment in Zucker fa/fa rats was seen. In agreement with our study, antioxidant effect of sesame oil and its polyphenolic compounds were documented in atherosclerotic and diabetic conditions [ 18 , 34 ] or in hyperlipidemic patients [ 24 ]. By reducing oxidative load, sesame oil may have direct activated effect on endothelial NOS leading to increase in NO production.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There were no significant changes in TBARS concentration within the groups; however, decreasing trend in TBARS concentration after SO treatment in Zucker fa/fa rats was seen. In agreement with our study, antioxidant effect of sesame oil and its polyphenolic compounds were documented in atherosclerotic and diabetic conditions [ 18 , 34 ] or in hyperlipidemic patients [ 24 ]. By reducing oxidative load, sesame oil may have direct activated effect on endothelial NOS leading to increase in NO production.…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, there are only limited data concerning the effects of sesame oil on NOS activity. Hsu and Parthasarathy [ 18 ] found that sesame oil significantly decreased lipid peroxidation but did not increase nitric oxide compared to N-acetyl cysteine. Sharma et al [ 32 ] have found an upregulation of eNOS in rats with cardiometabolic syndrome after sesamol treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sesame oil, known to have antioxidant effects associated with the characteristics of its components 5 . Sesame oil contains approximately 0.3-0.5% sesamolin, 1-4% sesamol and 0.5-1% sesamin 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sesame oil is a supplement with known anti-inflammatory properties and can reduce the risk of cardiovascular disease. Current studies have shown that this oil can reduce low-density lipoprotein (LDL) while maintaining high-density lipoprotein (HDL) levels [20]. Sesame oil is extremely resistant to oxidative rancidity [21].…”
Section: Introductionmentioning
confidence: 99%